2005
DOI: 10.1097/00005721-200507000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Preparedness

Abstract: Insight into the experiences of first-time mothers provides a framework for additional research and the development of programs and resources that will address their unique needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…Our results are consistent with other studies that have found that postpartum women feel inadequately prepared for the postpartum period [3, 1618]. Women in our maternal focus groups also expressed dissatisfaction with the communication and preparation they had received for discharge.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with other studies that have found that postpartum women feel inadequately prepared for the postpartum period [3, 1618]. Women in our maternal focus groups also expressed dissatisfaction with the communication and preparation they had received for discharge.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals asked to make multiple behavior changes report feeling confused and overwhelmed [ 39 ] and this may push them to quit and return to their unhealthy lifestyles. Particularly, because new mothers are facing a variety of stressors, including sleep deprivation, hormonal changes, and the demands of caring for a newborn [ 40 ]. In addition, body dissatisfaction and depression increases significantly during postpartum periods [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Informational support, particularly from health care providers, has long been thought to be important to new mothers to link them to broad and diverse information or to community resources. In addition, the provision of informational support, particularly through the educational and hands-on skills training sessions provided by nurses, has been considered an important component of the nurses’ role to facilitate the women’s transition to motherhood (George, 2005). There is some evidence that this type of support is associated with depressive symptoms during this transitional period.…”
Section: Introductionmentioning
confidence: 99%